POTRET PEKERJA MIGRAN DI PROVINSI JAWA BARAT - Budi Kusumo, Rani Andriani; Mukti, Gema Wibawa; Charina, Anne (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Migration is one of the strategies individuals or households pursue in the face of economic pressures. This paper aims to analyze the portrait of migrant workers in West Java Province. This paper was a literature study from various literature sources and secondary data sourced from the Central Statistics Agency (BPS), the Office of Manpower and Transmigration, as well as the Office of Service, Placement and Protection of Indonesia Migrant Workers (BP3MI) of West Java Province. Various things that could be expressed in this paper include the developing global economy, which impacts the sociocultural changes of society. In countries with better economic welfare, the demand for cheap labour to work in the informal sector continues to be formed, and among them is to replace the role of women in the domestic sphere. The decision of women to work as migrant workers was a rational act of individuals taking into account the benefits, costs and risks faced and influenced by various factors, including personal characteristics, values, family environment and also society, networks and also the demand for labour, and global economic conditions. Various data showed demand for Indonesian migrant workers to work in the domestic sector and less need for special skills; therefore, in recent years, portraits of Indonesian migrant workers, especially those from West Java, are still dominated by women working in the informal sector.